Bioefficacy of bioagents and botanicals against Colletotrichum dematium causing anthracnose of spinach - S.D. SOMWANSHI and P.S. NIKAM, V.B. BHUJBAL, A.P. SURYAWANSHI* (Indian Phytopathology, 2016)
Among various fungal diseases, anthracnose caused by Colletotrichum dematium is one of the devastating disease of spinach (Spinaceae oleraciae) crop. Present study was undertaken to evaluate in vitro bio-efficacy of bioagents and aqueous phytoextracts against C. dematium. Results revealed that among the test bioagents, significantly highest mycelial growth inhibition of the test pathogen was recorded with Trichoderma viride (70.00%), followed by Aspergillus niger (65.93%), T. harzianum (64.07%), T. hamatum (61.48%), T. longibrachitum (57.78%). All the test aqueous phytoextracts exhibited antifungal activity against the test pathogen and it was directly proportional to their concentrations. However, significantly highest mycelial growth inhibition was recorded with A. indica (60.74%), followed by A. satium (56.48%), O. sanctum (49.44%) and A. cepa (44.85%) and rest of the test phytoextracts recorded mycelial growth inhibition in the range of 18.15 to 45.00%.